Calcium Nanoparticles Impregnated With Benzenedicarboxylic Acid: A New Approach to Alleviate Combined Stress of DDT and Cadmium in Brassica alboglabra by Modulating Bioacummulation, Antioxidative Machinery and Osmoregulators - Mubeen, Samavia; Shahzadi, Iqra; Akram, Waheed; Saeed, Wajid; Yasin, Nasim Ahmad; Ahmad, Aqeel; Shah, Anis Ali; Siddiqui, Manzer H.; Alamri, Saud (Frontiers in Plant Science, 2022)
The alleviation of stress caused by climate change and environmental contaminants is a crucial issue nowadays. Dichlorodiphenyltrichloroethane (DDT) is a persistent organic contaminant (POP) and an organochlorine, that causes significant human health problems. Stress caused by cadmium (Cd), and the toxicity of DDT have direct effects on the growth and yield of the crop plants. Ultimately, the greater uptake and accumulation of DDT by edible plants affect human health by contaminating the food chain. The possible solution of this challenging situation is to limit the passive absorption of POPs into the plants. Calcium (Ca) is an essential life component mandatory for plant growth and survival. The current study used impregnated Ca (BdCa) of benzenedicarboxylic acid (Bd) to relieve abiotic stress in plants of Brassica alboglabra. BdCa mitigated the deleterious effects of Cd and reduced DDT bioaccumulation. By increasing the removal efficacy (RE) up to 256.14%, BdCa greatly decreased pollutants uptake (Cd 82.37% and DDT 93.64%) and supported photosynthetic machinery (86.22%), antioxidant enzyme defenses (264.73%), in applied plants. Exogenously applied Bd also successfully improved the antioxidant system, and physiochemical parameters of plants. However, impregnation with Ca further enhanced plant tolerance to stress. This novel study revealed that the combined application of Ca and Bd could effectively relieve individual and combined Cd stress and DDT toxicity in B. alboglabra.